MINAT SISWA DALAM PELAKSANAAN EKSTRAKURIKULER TARI DI SMP N 1 PADANG PANJANG - Ariep Bijaksana; Indrayuda Indrayuda; Zora Iriani (SENDRATASIK UNP, 2018)
AbstractThis article aims to explain the cause of his low-interest factor of students towards extracurricular activities 1 Junior High School dance in Padang Panjang. This type of research is qualitative research with a descriptive method. The object of the research was that students follow an extracurricular dance in SMP N 1 Padang Panjang. Instrument in this study is the researchers themselves by way of observation, documentation and interviews. The type of data in this study is the primary data and secondary data. Engineering data collection done by the library study, observation, documentation and interviews. The data has been collected, classified, diintrepresentasikan to avoid misinterpretation of data. The results showed that low cause factor of his interest in the activities of Esktrakurikuler students in Junior High School N 1 Padang Panjang there are 2 factors cause i.e. internal and external factors. Internal factors consist of desire, the attention and participation of external factors and consists of parents, coaches and facilities. The desires of the students in the following activities of the influential dance Estrakurikuler of these activities so that the stated desire of her low. Attention students in Extracurricular activities follow the Dance stated to have attention. Although there is still a small percentage of students who have not seriously followed the event. Participation of students extracurricular activities of dance graded fairly, although there are some students withdrew on the grounds there was les learning and there is no apparent reason.Keywords: Student Interest, implementation, Extracurricular Dance